1993
DOI: 10.1128/iai.61.5.1964-1971.1993
|View full text |Cite
|
Sign up to set email alerts
|

Protective salivary immunoglobulin A responses against Streptococcus mutans infection after intranasal immunization with S. mutans antigen I/II coupled to the B subunit of cholera toxin

Abstract: The B subunit of cholera toxin (CTB) has been shown to augment mucosal responses to microbial virulence antigens, including those of Streptococcus mutans, which is the principal etiologic agent of dental caries. In the present study, the surface fibrillar protein antigen of S. mutans, antigen I/II (Ag I/I), was chemically coupled to CTB (Ag I/I-CTB), and the conjugate was examined for its effectiveness in inducing salivary immune responses protective against S. mutans infection. Weanling Fischer rats were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 26 publications
1
60
1
Order By: Relevance
“…Since all 4 groups of animals had anti-GTF antibody activity and the levels were not significantly different, it is possible that a response resulted from infection with S. mutans. Previous studies have reported early serum responses in rats after infection with S. mutans (14). Serum IgA anti-GTF activity in these animals increased later (day 47) and were higher in the experimental groups than in the control group, although the differences between groups were not significant.…”
Section: Discussionmentioning
confidence: 61%
“…Since all 4 groups of animals had anti-GTF antibody activity and the levels were not significantly different, it is possible that a response resulted from infection with S. mutans. Previous studies have reported early serum responses in rats after infection with S. mutans (14). Serum IgA anti-GTF activity in these animals increased later (day 47) and were higher in the experimental groups than in the control group, although the differences between groups were not significant.…”
Section: Discussionmentioning
confidence: 61%
“…The Streptococcus mutans surface antigen AgI/II was originally identified as a potential antigen for developing a vaccine against caries (reviewed in Russell et al, 1999). We subsequently demonstrated that high levels of salivary IgA antibodies to AgI/II could be induced in rats or monkeys by mucosal immunization with AgI/II coupled to CTB, and that immunized rats were protected against caries (Katz et al, 1993;Russell et al, 1996). The N-terminal segment including the A-repeat region of AgI/II was found to be important in the adherence of S. mutans to saliva-coated hydroxyapatite (Hajishengallis et al, 1994), although others found that the central P-repeat region was also involved in adherence (Crowley et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal immunization can establish effective immunity against pneumococcal colonization in the upper respiratory tract, as well as protect mice from intratracheal challenge with virulent strains of pneumococci [5], block pharyngeal colonization by group A streptococci [6], protect mice from influenza virus infection [7], reduce Bordetella pertussis infection in mice [8], protect mice from i.n. herpes simplex virus challenge [9], and protect against Streptococcus mutans colonization on tooth surfaces [10,11]. However, the cells involved in generating this protection have not been defined.…”
Section: Introductionmentioning
confidence: 99%